2010
DOI: 10.1647/2008-041.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Cardiac Size in Four Falconiform Species

Abstract: To establish reference values for the cardiac size during radiographic examination in 4 species of Falconiformes used for falconry, lateral and ventrodorsal radiographs were examined from healthy birds of 4 species: Harris' hawks (Parabuteo unicinctus) (n = 48), peregrine falcons (Falco peregrinus) (n = 35), saker falcons (Falco cherrug) (n = 19), and lanner falcons (Falco biarmicus) (n = 13). On the lateral view, ratios between the length of the heart from base to apex and total length of the carina were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Beaufrère and Fitzgerald describe the larger hearts of wild cockatoos com-pared with captive species as sign of their cardiac fitness [19]. The falcon species studied in previous studies showed generally larger cardiac width than parrot species [6,9,13]. In Mirshahi et al [4] the width of the heart in wild common kestrels was larger compared to other falcon species, and in our study, our measured heart width was larger compared to that in other parrot species.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Beaufrère and Fitzgerald describe the larger hearts of wild cockatoos com-pared with captive species as sign of their cardiac fitness [19]. The falcon species studied in previous studies showed generally larger cardiac width than parrot species [6,9,13]. In Mirshahi et al [4] the width of the heart in wild common kestrels was larger compared to other falcon species, and in our study, our measured heart width was larger compared to that in other parrot species.…”
Section: Discussionsupporting
confidence: 55%
“…In non-parrot species, the cardiac/thoracic width ratio showed considerable variation. It is reported to be 45-59% in Humboldt penguins [8], 66-72% in saker falcons [9], 54-61% in Harris's hawks [9], 66-74% in peregrine falcons [9], 65-72% in lanner falcons [9], 48-57% in Bonelli's eagle [15], 67-69% in ospreys, 44-52% in bald eagles and 51-75% in common kestrels [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a total of 7 parrots in the patient group, both total cholesterol and triglycerides were elevated (no. 19,21,22,24,29,35,39).…”
Section: Patient Groupmentioning
confidence: 99%